Cross-Lingual Dependency Parsing of Related Languages with Rich Morphosyntactic Tagsets - Agić, Željko; Tiedemann, Jörg; Dobrovoljc, Kaja; Krek, Simon Merkler, Danijela; Može, Sara (2014)
This paper addresses cross-lingual dependency parsing using rich morphosyntactic tagsets. In our case study, we experiment with three related Slavic languages: Croatian, Serbian and Slovene. Four different dependency treebanks are used for monolingual parsing, direct cross-lingual parsing, and a recently introduced cross-lingual parsing approach that utilizes statistical machine translation and annotation projection. We argue for the benefits of using rich morphosyntactic tagsets in cross-lingual parsing and empirically support the claim by showing large improvements over an impoverished common feature representation in form of a reduced part-of-speech tagset. In the process, we improve over the previous state-of-the-art scores in dependency parsing for all three languages.
Projekt MZOS
ENG